Institutional impact of criminal networks in Colombia and Mexico - Garay Salamanca, Luis Jorge (Crime, law and social change, 2012)
This paper explores the effects of criminal networks involved in corruption and drug trafficking on democratic formal institutions in Colombia and Mexico. The theoretical framework is sustained in the concepts of State Capture (StC) and Co-opted State Reconfiguration (CStR). Three illicit networks are analyzed: (i) The Familia Michoacana in Mexico, (ii) the Autodefensas Campesinas del Casanare (ACC) in Colombia and (iii) the Autodefensas Unidas de Colombia (AUC). These cases are analyzed throughout the Social Network Analysis (SNA) in order to identify (i) the hub and (ii) the structural bridge of each network. A methodological variation referenced as Social Network Analysis for Institutional Diagnosis (SNAID) is also applied, in order to analyze the institutional scope of processes of StC and CStR. Conclusions and explorative venues regarding the application of SNA and SNAID as a diagnosis tool are presented.